2010
DOI: 10.1097/mpg.0b013e3181ca4d95
|View full text |Cite
|
Sign up to set email alerts
|

VSL#3 Improves Symptoms in Children With Irritable Bowel Syndrome: A Multicenter, Randomized, Placebo‐Controlled, Double‐Blind, Crossover Study

Abstract: : VSL#3 is safe and more effective than placebo in ameliorating symptoms and improving the quality of life in children affected by IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
155
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(169 citation statements)
references
References 32 publications
2
155
0
12
Order By: Relevance
“…Thirteen articles remained for analysis: 7 systematic reviews 11,12,15,16,18,22,23 (including 18 RCTs) and 6 RCTs. [24][25][26][27][28][29] Two included trials concerned follow-up studies, 26,30 which will be discussed by using their original studies. 31,32 Two systematic reviews 11,12 included studies with ,10 patients per treatment arm, and these studies were therefore excluded.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirteen articles remained for analysis: 7 systematic reviews 11,12,15,16,18,22,23 (including 18 RCTs) and 6 RCTs. [24][25][26][27][28][29] Two included trials concerned follow-up studies, 26,30 which will be discussed by using their original studies. 31,32 Two systematic reviews 11,12 included studies with ,10 patients per treatment arm, and these studies were therefore excluded.…”
Section: Resultsmentioning
confidence: 99%
“…40,41 The method of randomization was unclear in 3 studies. 27,31,50 Alfvén and Lindstrom 48 provided no information on outcome blinding or treatment duration. Six trials did not present results with absolute numbers and were therefore not included in the meta-analysis.…”
Section: Methodologic Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…In this study total of 59 children were evaluated and abdominal pain, abdominal bloating/gassiness and family assessment of life disruption were improved significantly. 31 In a randomized study involving 78 children (total of 345 children aged 4-18 years) with IBS, there was seen clinical recovery 94.9% of 39 children treated with trimebutine maleate. Authors concluded that trimebutine maleate is an effective agent for treating childhood IBS.…”
Section: Treatmentmentioning
confidence: 99%